Pattern Catalogs using the Pattern Language Meta Language - Wolff, Andreas; Forbrig, Peter (Electronic Communications of the EASST, 2010)
This article focuses on the pattern language PLML. Some enhancements and corrections to it are proposed to make use of PLML in pattern catalogs. Additionally, a textual domain specific language as human-readable variant of PLML is proposed. Supporting editors, textual and graphical, which were developed using model-based techniques are presented.